2002
DOI: 10.1089/089771502753594873
|View full text |Cite
|
Sign up to set email alerts
|

Craniectomy Position Affects Morris Water Maze Performance and Hippocampal Cell Loss after Parasagittal Fluid Percussion

Abstract: Valid and reliable animal models are essential for mechanistic and therapeutic studies of traumatic brain injury (TBI). Therefore, model characterization is a continual and reciprocal process between the experimental laboratory and the clinic. Several excellent experimental models of TBI, including the lateral fluid percussion rat model, are currently in wide use in many neurotrauma laboratories. However, small differences in the position of lateral fluid percussion craniectomy are reported between labs. Addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(64 citation statements)
references
References 22 publications
3
61
0
Order By: Relevance
“…Although a selective downregulation of Nogo-A in hilar neurons cannot be excluded, neuronal cell death in the hilus of the dentate gyrus is a well-known consequence of lateral fluid percussion brain injury (Lowenstein et al, 1992;Hicks et al, 1993;Floyd et al, 2002), likely accounting for the observed changes in Nogo-A expression. In addition, we observed numerous Nogo-A (+) processes in the subgranular layer (SGL) of the dentate gyrus emerging post-injury.…”
Section: Discussionmentioning
confidence: 99%
“…Although a selective downregulation of Nogo-A in hilar neurons cannot be excluded, neuronal cell death in the hilus of the dentate gyrus is a well-known consequence of lateral fluid percussion brain injury (Lowenstein et al, 1992;Hicks et al, 1993;Floyd et al, 2002), likely accounting for the observed changes in Nogo-A expression. In addition, we observed numerous Nogo-A (+) processes in the subgranular layer (SGL) of the dentate gyrus emerging post-injury.…”
Section: Discussionmentioning
confidence: 99%
“…Within experiments, direct force onto the brain imparts highly reproducible focal damage, though changes in craniotomy position translate to variable outcomes between laboratories. 39 In the LFP model, a pendulum strikes a fluid-filled reservoir, and pressure from a fluid-filled bolus is forced into the epidural space, 37,40 The LFP model typically induces focal damage such as hemorrhage and edema at the site of impact, with progressive subcortical cell death, [41][42][43] thereby replicating many structural, pathological, and neurobehavioral features of moderatesevere human TBIs. LFP has been used to model single 44 and repeated mTBI, [45][46][47] by lowering the pendulum height to reduce the pressure pulse and therefore injury severity.…”
Section: Open-head Models Of Tbimentioning
confidence: 99%
“…Fluid percussion injury was carried out as described previously. [18][19][20] Briefly, rats were initially anesthetized using 5% isoflurane with a 1:1 N 2 O/O 2 mixture and then maintained with a 2.5% isoflurane with 1:1 N 2 O/O 2 mixture via a face mask. Animals were mounted on the stereotaxic frame, a midline 4.8 mm-diameter craniectomy was carefully made midway between bregma and lambda.…”
Section: Lateral Fluid Percussion Injurymentioning
confidence: 99%